PACK CARBURIZING USING COCONUT SHELL CHARCOAL AND EAST AFRICAN SNAIL SHELL AS ENERGIZER TO 2.6 MM DIAMETRE LOW CARBON STEEL HELICAL SPRING - UM SIMANGUNSONG (NIM : 13102138); Dosen Pembimbing I : Dr. Ir. Budi Hartono Setiamarga Dosen , BOY
Spring is a mechanical element that is used in many kinds of application. Spring usually is made from expensive spring steel material. In this project, springs made from low carbon steel wire were pack carburized, quenched, and tempered, to reach the same level of strength and hardness as spring steel. This project investigates the relationship of carburizing time and tempering temperature with spring constant value. In this research, low carbon steel wire was coiled into spring, and carburized using 90%wt coconut charcoal and 10% wt East African snail shell energizer. These springs were pack carburized with three variation of holding time, those are 10 minutes, 15 minutes, and 20 minutes. After carburized, spring was treated with quench hardening to increase hardness on it’s surfaces. To increase the ductility and toughness, tempering is applied into the spring. Tempering is held in three level of temperature, those are: 300 oC, 350 oC, and 400 oC. The hardness distributions from the surface of the samples were measured in order to know the effect of the previous processes. Loading tests were then done in order to find the spring’s stifness constant value. From calculation, it is concluded that hardness value and spring’s stifness constant is proportional with carburizing holding time, and inversely proportional with tempering temperature.